Risk Analysis and Mitigation Strategy at Bank Muamalat KCP Sepanjang - Amelia Zahranita Auri; Sri Wigati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the different kinds of risks that Bank Muamalat KCP Sepanjang faces as well as the mitigation strategies implemented to manage these risks. This research uses qualitative methods with a descriptive approach to understand risk phenomena in depth through interviews and observations. The research results show that Bank Muamalat faces several main risks, including credit risk, market risk, liquidity risk and strategic risk. Strategic risk is the biggest challenge because it requires adjustments to changes in business competition, innovation and technological developments. The mitigation strategies implemented by Bank Muamalat include strict supervision of strategic policies, collaboration with other parties, and adaptation to new technology. With the right mitigation strategy, Bank Muamalat KCP Sepanjang can maintain its stability and growth in the sharia banking sector.